2007
DOI: 10.1111/j.1475-2743.2007.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of an electromagnetic technique to determine sodicity in saline‐sodic soils

Abstract: Soil sodicity is an increasing problem in arid‐land irrigated soils that decreases soil permeability and crop production and increases soil erosion. The first step towards the control of sodic soils is the accurate diagnosis of the severity and spatial extent of the problem. Rapid identification and large‐scale mapping of sodium‐affected land will help to improve sodicity management. We evaluated the effectiveness of electromagnetic induction (EM) measurements in identifying, characterizing and mapping the spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
2
11
1
Order By: Relevance
“…Nonetheless, the significant positive correlation between EC a and soil properties indicated that an electromagnetic induction survey is an effective technique to capture the geospatial variability in the soil properties. Our findings of a strong correlation between EC e and SAR in soils of arid regions have also been reported by several other authors (Corwin et al, 2003;Amezketa, 2007;Ganjegunte et al, 2014). In areas where salts in the soil are accumulated due to evapo-concentration, EC e and SAR were strongly correlated because of the selective precipitation of Ca minerals in the concentrated soil solution, especially if there are considerable amounts of carbonates.…”
Section: Irrigation Water Quality Apparent Electrical Conductivity Dsupporting
confidence: 90%
See 2 more Smart Citations
“…Nonetheless, the significant positive correlation between EC a and soil properties indicated that an electromagnetic induction survey is an effective technique to capture the geospatial variability in the soil properties. Our findings of a strong correlation between EC e and SAR in soils of arid regions have also been reported by several other authors (Corwin et al, 2003;Amezketa, 2007;Ganjegunte et al, 2014). In areas where salts in the soil are accumulated due to evapo-concentration, EC e and SAR were strongly correlated because of the selective precipitation of Ca minerals in the concentrated soil solution, especially if there are considerable amounts of carbonates.…”
Section: Irrigation Water Quality Apparent Electrical Conductivity Dsupporting
confidence: 90%
“…In recent years, the EC e Sampling Assessment and Prediction (ESAP) model, developed by the U.S. Department of Agriculture's Salinity Laboratory, is gaining popularity and has been successfully used for delineating the spatial distributions of soil properties from EC a survey data (Lesch, 2006;Ganjegunte and Braun, 2011;Ganjegunte et al, 2013). A strong correlation (e.g., 0.89 in Ganjegunte et al (2013) between EC e and sodium adsorption ratio (SAR) observed in many arid regions indicate that EMI data can also be used to determine spatial distribution of sodicity (Amezketa, 2007).…”
Section: Soil Salinity Of An Urban Park After Long-termmentioning
confidence: 99%
See 1 more Smart Citation
“…A strong correlation between EC e and SAR explained the significant positive relationship between EC a and SAR. Other researchers have also found strong correlations between EC a readings and SAR (Nelson et al, 2002;Corwin and Lesch, 2005b;Corwin et al, 2006;Amezketa, 2007). The coefficients of determination for EC e and SAR were significant; however, due to the sandy loam texture of the soil present in this study, the proportion of the variability explained by the models was not as high as R 2 reported for fine-textured soils (Ganjegunte and Braun, 2011;Ganjegunte et al, 2013).…”
Section: Electromagnetic Induction Measurements In Soil Salinity and contrasting
confidence: 47%
“…Although EC a is generally used for measuring soil salinity, it can also be used to determine spatial distribution of SAR, if there is a strong correlation between EC e and SAR (Amezketa, 2007). Currently, information is lacking whether or not remote sensing EMI technology can be used to track soil salinity in landscape areas that are irrigated with saline water.…”
mentioning
confidence: 99%